Adolescent sleep and its disruption in depression and anxiety - Chai, Ruiming; Bian, Wen-Jie (Frontiers in Neuroscience, 2024)
Adolescence is a pivotal stage during development when one’s personality, emotion, and behavioral traits are shaped to a great extent, and the underlying neural circuits undergo substantial developmental organizations. Dramatic and dynamic changes occur in sleep architecture throughout the postnatal developmental course. Insufficient sleep and disruption of sleep/wake coherence are prevalent among the adolescents worldwide, and even so in young patients with neuropsychiatric conditions. Although accumulating evidence has suggested a tight association between sleep disruption and depression/anxiety, the causal relationship remains largely unclear. More importantly, most of these studies focused on adult subjects, and little is known about the role of sleep during the development of mood and behavior. Here we review recent studies investigating the acute and chronic effects of adolescent sleep disruption on depression and anxiety both in humans and rodent models with focuses on the assessment methodology and age. By discussing the findings and unsolved problems, we hope to achieve a better understanding of the relationship between sleep and mental health in adolescents and provide insights for future research.